MANAJEMEN DINAS PERTANIAN DAN PANGAN KOTA BUKITTINGGI DI BIDANG KETAHANAN PANGAN TAHUN 2021-2023 - Ramdani, Jufri; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Food security is a strategic issue that requires serious attention, especially amid the threats of inflation, climate change, limited land, and distribution disruptions. This research aims to describe the management of the Agriculture and Food Office of Bukittinggi City in the field of food security from 2021 to 2023. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, documentation, and literature studies. The results show that the Agriculture and Food Office of Bukittinggi City has implemented managerial functions including planning, organizing, executing, and supervising food security programs. Various programs such as the Affordable Food Movement, provision of superior seeds, local food diversification, and farmer empowerment have been carried out to strengthen food security. However, several challenges still hinder the achievement of targets, such as the limited area of agricultural land, high inflation, pest attacks, and climate change. Keywords: Management, food security, local government, governance management.